420 nm thick CH3NH3PbI3−xBrx capping layers for efficient TiO2 nanorod array perovskite solar cells*Project supported by the National Natural Science Foundation of China (Grant Nos. 51472071 and 51272061) and Talent Project of Hefei University of Technology, China (Grant Nos. 75010-037004 and 75010-037003). (January 2018) - Li 李, Long 龙; Shi 史, Cheng-Wu 成武; Deng 邓, Xin-Lian 新莲; Wang 王, Yan-Qing 艳青; Xiao 肖, Guan-Nan 冠南; Ni 倪, Ling-Ling 玲玲
Abstract : The rutile TiO2 nanorod arrays with 240 nm in length, 30 nm in diameter, and 420 μ m − 2 in areal density were prepared by the hydrothermal method to replace the typical 200–300 nm thick mesoporous TiO2 thin films in perovskite solar cells. The CH3 NH3 PbI3− x Br x capping layers with different thicknesses were obtained on the TiO2 nanorod arrays using different concentration PbI 2 · DMSO complex precursor solutions in DMF and the photovoltaic performances of the corresponding solar cells were compared. The perovskite solar cells based on 240 nm long TiO2 nanorod arrays and 420 nm thick CH3 NH3 PbI3− x Br x capping layers showed the best photoelectric conversion efficiency (PCE) of 15.56% and the average PCE of 14.93±0.63% at the relative humidity of 50%–54% under the illumination of simulated AM 1.5 sunlight ( 100 mW · cm − 2 ).